Vivências e desafios: um olhar sobre a sexualidade e envelhecimento de mulheres lésbicas - Bernardi, Larissa Sasso (2024)
When thinking about aging and sexuality contemporaneously, the possibility of questioning female homosexuality and how the aging process can affect these subjects opens up. Thus, this dissertation has as its starting point qualitative and field research, whose general objective is to understand the self-perception of lesbian women in an aging process close to what is considered old age, in relation to their sexuality. Your goals Specific aspects are: understanding how older lesbian women experience love; identify the existence of supportive relationships in the families of lesbian women, regarding their sexuality; investigate the presence of violence, prejudice and microaggressions; analyze how participants perceive prejudices related to sexuality and aging. The study population consisted of lesbian women in the aging process close to what is considered old age, from 55 years of age onwards. The sample consisted of six women, defined by the snowball method, who were interviewed based on a semi-structured script of questions. Data analysis was carried out through the analysis of discursive practices proposed by Spink and Medrado (2000). The research gave rise to a scientific article, which presents the main findings of the investigation carried out. Thus, as a result, we observe the pluralities in aging and how issues relating to sexuality are present from family relationships to broader social relationships established. The search allows us to conclude that these women experience supportive relationships, love, prejudice, social and family non-acceptance, their experiences in relation to sexuality and aging are shaped by their personal experiences. Therefore, these subjects experience their sexuality and aging according to their stories. For new research horizons, the need arises to reflect on the difficult access to the target audience of the investigation, which was a limit of the research, suggesting the existence of a population of lesbian women in the aging process, and what are the relationships between this and the values ​​and beliefs of each historical time in society, as there seems to be an invisible population made up of elderly lesbian women, whose aging needs to be made visible and cared for in order to promote quality of life.